The impact of digitalisation on Danish companies and workers - Saman Darougheh; Filip Rozsypal (Danmarks Nationalbank, 2022)
This memo explores the impact of digitalisation on Danish workers and companies. For this, we first build two complementary measures of digitalisation that leverage Danish administrative data. We then document a positive association between the level of digitalisation and sales of large companies. In the final part, we study the workers in the IT sector – the producers of the digital tools. We find that the workforce in the IT sector is more specialised than the rest of the Danish workforce, and that this specialisation has increased during the past decade.
Keywords: 330; Danish Economy; Digitalisation